Identification of Novel Mitochondrial Protein Components of Chlamydomonas reinhardtii. A Proteomic Approach - van Lis, Robert (American Society of Plant Biologists, 2003)
Pure mitochondria of the photosynthetic alga Chlamydomonas reinhardtii were analyzed using blue native-polyacrylamide gel electrophoresis (BN-PAGE). The major oxidative phosphorylation complexes were resolved: F(1)F(0)-ATP synthase, NADH-ubiquinone oxidoreductase, ubiquinol-cytochrome c reductase, and cytochrome c oxidase. The oligomeric states of these complexes were determined. The F(1)F(0)-ATP synthase runs exclusively as a dimer, in contrast to the C. reinhardtii chloroplast enzyme, which is present as a monomer and subcomplexes. The sequence of a 60-kD protein, associated with the mitochondrial ATP synthase and with no known counterpart in any other organism, is reported. This protein may be related to the strong dimeric character of the algal F(1)F(0)-ATP synthase. The oxidative phosphorylation complexes resolved by BN-PAGE were separated into their subunits by second dimension sodium dodecyl sulfate-PAGE. A number of polypeptides were identified mainly on the basis of their N-terminal sequence. Core I and II subunits of complex III were characterized, and their proteolytic activities were predicted. Also, the heterodimeric nature of COXIIA and COXIIB subunits in cytochrome c oxidase was demonstrated. Other mitochondrial proteins like the chaperone HSP60, the alternative oxidase, the aconitase, and the ADP/ATP carrier were identified. BN-PAGE was also used to approach the analysis of the major chloroplast protein complexes of C. reinhardtii.